2018
DOI: 10.1515/cjot-2018-0008
|View full text |Cite
|
Sign up to set email alerts
|

Zoo Tourism: What Actually Is a Zoo?

Abstract: Zoos are one of the most visited tourist attractions worldwide - we should perceive them, therefore, not only as places where animals are kept, but also as places frequented by large numbers of people. This is why we talk of zoo tourism. However, there are different definitions of a zoo. This wide range of possible approaches to what actually the zoo is poses a major methodological problem for the research analysis as well as for the zoo management and related legislation. Zoos are historically and socially de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…The education level of visitors at the secondary and higher education levels showed the characteristics of visitors as the basis for developing insight and knowledge, especially related to animal conservation, for example through research activities and educational tours. Nekolny and Fialova (2018) stated that a zoo is a special cultural and educational facility that has four main tasks, namely: conservation of endangered species, science and research, education, and human recreation. Collins et al (2019) added that currently intervention in the world of education is an effort to reduce negative behavior of visitors and improve animal welfare positively.…”
Section: Methodsmentioning
confidence: 99%
“…The education level of visitors at the secondary and higher education levels showed the characteristics of visitors as the basis for developing insight and knowledge, especially related to animal conservation, for example through research activities and educational tours. Nekolny and Fialova (2018) stated that a zoo is a special cultural and educational facility that has four main tasks, namely: conservation of endangered species, science and research, education, and human recreation. Collins et al (2019) added that currently intervention in the world of education is an effort to reduce negative behavior of visitors and improve animal welfare positively.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the 15 traditional zoos founded before 1989, 14 official zoos were established after 1989, but one of them (Terarium Praha) had actually been closed to the public since the spring of 2019. For the sake of comparability, only zoos considered as zoological gardens according to the Nekolný and Fialová [32] typology were included in the research. Thus, indoor exhibitions such as aquariums and terrariums with another regime of re-opening were excluded.…”
Section: Study Areamentioning
confidence: 99%
“…Some animal houses can even experience a long-term change in their visitor numbers [30]. Methodology (e.g., including paying vs all visitors, annual passes) can also be important [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Conservation institutions are special cultural and educational facilities with four main tasks: conservation of endangered species, science and research, education, and human recreation (Nekolny and Fialova 2018). Collins et al (2019) revealed that the current intervention in the world of education is an effort to reduce negative visitor behavior and improve animal welfare.…”
Section: Animal Welfare Implementation At Trm Serulingmasmentioning
confidence: 99%